Serum and synovial lactate dehydrogenase levels after allogeneic mesenchymal stem cell implantation in rabbit cartilage defects - Anatolitou, A.; Mavrogenis, A.F.; Sideri, K.I.; Psalla, D.; Markou, M.; Prassinos, N.N. (Polish Journal of Veterinary Sciences, 2026)
Cartilage defects have limited regenerative potential and remain a significant clinical challenge. Mesenchymal stem cell (MSC) therapy offers promise in tissue engineering, yet monitoringpost-implantation responses remains difficult. Lactate dehydrogenase (LDH), a biomarkerof cell damage and inflammation, may provide insight into systemic and local tissue reactions. This study aimed to assess the levels of serum and synovial fluid LDH following the implantation of allogeneic MSCs into cartilage defects in a rabbit model. A total of 56 New Zealand white rabbits were randomly divided into four groups: control (Group A), and groups receiving fibrin glue with adipose-derived stem cells (ASCs), bone marrow-derived stem cells (BMSCs), or synovial-derived stem cells (SDSCs). Serum and synovial fluid samples were collected at baseline and 12 weeks post-surgery to measure serum and synovial fluid LDH levels. Serum LDH levels were significantly elevated in all MSC-treated groups relative to controls (p=0.019), potentially due to high anaerobic metabolism or implantation-related toxicity, systemic response and apoptosis. However, no additional adverse effects were observed, making toxicity or further articular damage unlikely. No significant changes were detected in synovial fluid LDH across groups (p=0.070), suggesting limited value as a biomarker for cartilage repair.